Cognitive and motor aspects of cancer‐related fatigue - Feng, Li Rebekah (Cancer Med, 2019)
BACKGROUND: Cancer‐related fatigue (CRF) is a debilitating symptom frequently reported by patients during and after treatment for cancer. CRF is a multidimensional experience and is often solely assessed by self‐report measures. The goal of the study is to examine the physical and cognitive aspects of self‐reported CRF using a cognitive function test and a physical fatigue index in order to provide objective measures that can characterize the CRF phenotype. METHODS: A total of 59 subjects with nonmetastatic prostate cancer receiving external beam radiation therapy were included in the study. Fatigue was measured using the Functional Assessment of Cancer Therapy‐Fatigue (FACT‐F) questionnaire. Cognitive characteristics of CRF was measured using the Stroop Color‐Word Interference computerized test and the motor aspect of fatigue was measured using the static fatigue test using a handgrip dynamometer. FINDINGS: Functional Assessment of Cancer Therapy‐Fatigue scores significantly correlated with the Stroop Interference score, but not performance accuracy in all test conditions. Fatigued subjects exhibited a more rapid decline to 50% of maximal strength and increased static fatigue index in the handgrip test, whereas maximal grip strength was not affected. CONCLUSIONS: The results suggest that CRF exhibits both cognitive and physical characteristics. Subjective fatigue was associated with increased time required to overcome cognitive interference, but not cognitive performance accuracy. Fatigued patients exhibited decreased physical endurance and the ability to sustain maximal strength over time. These objective measures may serve as valuable tools for clinicians to detect cognitive and physical impairment associated with CRF.